Effect of 17β-Estradiol on Feminization, Growth Rate and Survival Rate of Pacific White Shrimp (Litopenaeus vannamei, Boone 1931) Postlarvae - Sugestya, I Nengah Gde; Widodo, Maheno Sri; Soeprijanto, Agoes (Graduate School, Universitas Brawijaya, 2018)
This study was therefore aimed to determine the effect of different concentration of estrogen hormone, 17β-estradiol (E2) on feminization for the production of all female, growth rate and survival rate of Pacific white shrimp (Litopenaeus vannamei) postlarvae (PL). L. vannamei PL1 were stocked randomly at a density of 10 ind.L-1 into a 10 L of seawater for each experimental flask with three replicates each. PL1 was immersed in seawater containing 0.5, 1.0 and 1.5 mg.L-1 estrogen hormone, E2 for 4 hours. The experiment was continued for 30 days for larval rearing. At the termination of experiment, the specimens in each treatment groups were weighed and measured individually for their wet body weight (BW) and total length (TL) for the mean weight gain, length gain, and the specific growth rate (SGR) estimation. The mean sex ratio values of male to female postlarvae obtained from control till the highest E2 hormone concentration of 0, 0.5, 1.0 and 1.5 mg.L-1 were 1:1, 1:2, 1:9 and 0:1 respectively. The weight gain and length gain were 40605% and 606% for control, 46310% and 647% for 0.5 mg.L-1 concentration, 49310% and 663% for 1.0 mg.L-1 concentration and 45048% and 628% for 1.5 mg.L-1. The mean SGR BW and SGR TL for control till the highest E2 hormone concentration of 0, 0.5, 1.0 and 1.5 mg.L-1 were 20.00 and 6.51, 20.46 and 6.70, 20.67 and 6.77 and 20.37 and 6.62 respectively. The mean survival rate for E2 hormone concentration of 0, 0.5, 1.0 and 1.5 mg.L-1 were 52.67%, 54.33%, 54.67% and 52.33% respectively. The study shows that while the concentration of E2 hormone increased, the female sex ratio of L. vannamei PL also increased but the growth rate and survival rate decreased at concentration of 1.5 mg.L-1. Thus the optimum concentration of this hormone usage was 1.0 mg.L-1 immersed for 4 hours. Keywords: 17β-estradiol, feminization, growth rate, Litopenaeus vannamei, postlarvae, survival rate.